Kombinasi Protokol Routing OSPF dan BGP dengan VRRP, HSRP, dan GLBP - Debbi Irfan Mudhoep; Linawati; Oka Saputra (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2021)
Vocational High Schools as educational institution that adopt vocation based curriculum get the advantages and benefits of the development of the teaching factory. Teaching factory is a product and business oriented concept of learning in response to the challenges and development of the industry. However, during the pandemic period, teaching factory management faces many obstacles, one of which is in the performance of the network. The current network uses static routing network protocol which has no backup line or track. It is, therefore, suggested to apply dynamic routing OSPF and BGP with the VRRP, HSRP, and the GLBP workload method as the backup line which is measured through the throughput, delay, and packet loss parameter, for its Quality of Service (QoS). The research scenario stage applies each routing protocol to each performance method, so that it can be measured to obtain the expected QoS results at end users. The best result that will be recommended is routing OSPF by VRRP method because it has less than 1 second time comparison when there is a network failure. It is shown in the QoS result of 3.96, which shows that it is very satistactory compared to others.